HUBUNGAN PENGETAHUAN DAN SIKAP TERHADAP KEBIASAAN REMAJA PUTRA MEROKOK DI SMAN 2 TUALANG - Dwiana Indah Lestari (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
Abstract : According to the Indonesian Ministry of Health in 2010 stated that in Indonesia, approximately 70% of smokers start the habit before the age of 19 years. The proportion of new smokers continue to grow while the group of younger children aged 5-9 years. Subdistrict Tualang Siak that society also consists of mostly teenagers who are studying there at some High School is one of SMAN 2 Tualang, the strategic location of the District Tualang are usually used student as a gathering place very high risk encouraging increased naughtiness such as smoking in adolescents. The purpose of this study was to determine the relationship between knowledge and attitudes towards smoking habits of young men in SMAN 2 Tualang 2014.This type of research is the design of Analytical and quantitative cross-sectional approach. The total sample of 75 respondents from 293 population sampling by means of random sampling. Univariate analysis was used and the Bivariate chi-square test to determine the relationship between knowledge and attitudes towards smoking habits of young men. The results of this study showed a significant relationship between knowledge of knowledge of the smoking habits of young men, with the value of pvalue = 0.035 and OR = 1,357 value. and the existence of a significant relationship between attitude attitudes towards smoking habits of young men with values pvalue = 0.010 and OR = 6,067 value. Therefore we can conclude the results of research in SMAN 2 Tualang that there is a relationship of knowledge and attitudes towards smoking habits of young men, that respondents with low knowledge have the opportunity to perform 1,357 times smoking habits, and attitudes of respondents who have agreed to have the opportunity to take action 6,067 times the smoking habit. Suggested for respondents to be able to attend the seminar on lung health associated with smoking. Keywords : Relationship, knowledge, attitude, teen smoking